PERAN GURU DALAM PEMERTAHANAN RAGAM BAHASA BALI - I Nengah Adi Widana (Subasita: Jurnal Sastra Agama dan Pendidikan Bahasa Bali, 2020)
Balinese language is one of the regional languages in Indonesia, which is not only a reflection of a community, but also a reflection of all aspects of people's lives. As one of the regional languages, Balinese language has variations or variations of languages. The variety of Balinese languages can be seen regionally can be divided into two major variations namely the mountainous dialect and the Balinese dialect, each of which has a subdialect. The range of mountain dialects is also called the village dialect (characteristic of certain villages/regions), while the Balinese dialect of the plains develops into Sor Singgih Basa Bali which consist of several levels including basa kasar, basa andap, basa madia, basa alus and basa mider. There are a lot of varieties of Balinese languages that as a teacher has the role of maintaining the Balinese language by acting as a facilitator, motivator, booster, learning engineer and learning inspiration for students. Keywords: Teachers, Retention, Variety of Balinese Language